On the absence of triplet exciton loss pathways in non-fullerene acceptor based organic solar cells. Issue 6 (21st April 2020) - Kotova, Maria S.; Londi, Giacomo; Junker, Johannes; Dietz, Stefanie; Privitera, Alberto; Tvingstedt, Kristofer; Beljonne, David; Sperlich, Andreas; Dyakonov, Vladimir
Abstract : Recombination to donor and acceptor triplet states should be energetically favourable. However, this recombination channel is not observed in operational devices. Abstract : We investigate the viability of highly efficient organic solar cells (OSCs) based on non-fullerene acceptors (NFA) by taking into consideration efficiency loss channels and stability issues caused by triplet excitons (TE) formation. OSCs based on a blend of the conjugated donor polymer PBDB-T and ITIC as acceptor were fabricated and investigated with electrical, optical and spin-sensitive methods. The spin-Hamiltonian parameters of molecular TEs and charge transfer TEs in ITIC e.g., zero-field splitting and charge distribution, were calculated by density functional theory (DFT) modelling. In addition, the energetic model describing the photophysical processes in the donor–acceptor blend was derived. Spin-sensitive photoluminescence measurements prove the formation of charge transfer (CT) states in the blend and the formation of TEs in the pure materials and the blend. However, no molecular TE signal is observed in the completed devices under working conditions by spin-sensitive electrical measurements. The absence of a molecular triplet state population allows to eliminate a charge carrier loss channel and irreversible photooxidation facilitated by long-lived triplet states. These results correlate well with the high power conversion efficiency of the PBDB-T:ITIC-based OSCs and their high stability.